Analysis of the Variables that Affect Bookstore Customer Satisfaction - Wulan, Elis Ratna; Husaeni, Uus Ahmad (International Journal of Nusantara Islam, 2015)
Competition, which becomes more widespread, complex, and intense, drives companies to must be able to see the various opportunities that exist and to identify strategies for creating customer satisfaction. As an example of a company must be able to produce products with good quality, reasonable price, facilities, and companies are able to create a positive image in the eyes of consumers. This strategy is quite important in facing the competitive level of competition with rival firms. This research is aimed to analysis simultaneously or partially positive effect of the facilities, prices and corporate image on customer satisfaction, as well as analyzing the most dominant variable in effecting bookstore customer satisfaction. Data used in this research are primary data from Tmbookstore customer in Cianjur city, West Java Indonesia, which were collected from respondents using valid and reliable questionnaire. A total of 100 respondents were selected from Tmbookstore visitors by accidental sampling. Data were analyzed using multiple regression analysis. Results of the research indicate that product, price, location, and simultaneously affect to bookstore consumer satisfaction. Partially, only two of the three variables that affect bookstore consumer satisfaction namely price and company image. Image of the company is the most a dominant impact on bookstore customer satisfaction.